Need Frustration and Poor Mental Health Among Collegiate Athletes: The Indirect Role of Ruminative Thinking - Alanni Brown; Adrian Bravo (Journal of Athlete Development and Experience)
Vulnerability to negative mental health outcomes (i.e. anxiety and depression) among DI collegiate athletes may best be understood using Self Determination Theory (SDT) and the framework that need frustration impairs autonomy, competence, and relatedness. Need frustration may also relate to negative mental health symptoms via higher ruminative thinking, known to relate to both need frustration and poor mental health. The present study tested these two path models (i.e., SDT need frustration components [autonomy, relatedness, competency]-->rumination facets [problem-focused thoughts, counterfactual thinking, repetitive thinking, anticipatory thoughts]-->mental health problems (one for depression and one for anxiety as outcomes) among 341 collegiate athletes (65.6% female) who participated in a DI varsity sport. Within our depression model, there were no significant indirect effects between need frustration components and depressive symptoms via rumination facets. Regarding our anxiety model, several indirect effects were found such that higher scores on autonomy and competency frustration were associated with higher endorsement of two rumination facets (problem-focused thoughts and repetitive thoughts), which in turn were associated with greater endorsement of anxiety symptoms. Future research should be conducted to evaluate other factors to design proper interventions to help reduce symptomology for anxiety and depression among collegiate athletes.